Lung uptake of two SPECT markers identifies sensitivity to hyperoxia-induced acute respiratory distress syndrome in rats - Clough, Anne V.; Taheri, Pardis; Sharma, Guru P.; Zhao, Ming; Jacobs, Elizabeth R.; Audi, Said H. (Frontiers in Physiology, 2025)
IntroductionExposure of adult rats to hyperoxia is a well-established model of human Acute Respiratory Distress Syndrome (ARDS). Although rats exposed to 100% O2 display clinical evidence of lung injury after ∼40 h and death by 72 h, rats exposed to 60% O2 for up to 7 days show little sign of injury. However, when subsequently exposed to hyperoxia, these pre-exposed rats become more susceptible to ARDS. The objective of this study is to evaluate the ability of imaging biomarkers to track this hyperoxia susceptibility and to elucidate underlying mechanisms.MethodsSprague-Dawley rats were exposed to either room air (normoxia), >95% O2 for 24 h (hyperoxia), 60% O2 for 7 days (H-S), or H-S followed by 24 h of hyperoxia (H-S+24). Following i.v. injection of 99mTc-duramycin (marker of cell death) and/or 99mTc-hexamethylpropelyneamine oxime (99mTc-HMPAO, marker of lung tissue redox status), in vivo scintigraphy images were acquired and lung uptake of these biomarkers was determined from the images. Results99mTc-HMPAO uptake was 84% greater in hyperoxic rats compared to normoxic controls. Uptake in H-S rats was 34% higher than normoxics, but with no change with subsequent exposure to hyperoxia (H-S+24). 99mTc-duramycin uptake was 40% greater in hyperoxic rats than normoxics. Uptake in H-S rats was not different from normoxics but increased by 160% with H-S+24 in conjunction with enhanced hyperoxia susceptibility. 99mTc-HMPAO and 99mTc-duramycin uptake correlated with expression of 3-nitrotyrosine (oxidative stress) and cleaved-caspase 3 (cell death) measures acquired independently. DiscussionOverall, these results suggest the potential utility of 99mTc-HMPAO and 99mTc-duramycin imaging for identifying those hosts that are more, or less, susceptible to progression to severe ARDS at a time of mild symptoms of lung injury.